KOMITMEN DAN PERILAKU KERJA GURU DI SEKOLAH DASAR NEGERI 3 KEMUNING BANJARBARU - FARIDAH KARYATI (Pahlawan, 2019)
This study aims to determine the description of teacher commitment, know the description of teacher work behavior, and find out whether there is a relationship between commitment and work behavior of teachers in SDN 3 Kemuning Banjarbaru. The population amounted to 16 teachers who were the samples in this study. The data digging tool used in this study is a questionnaire as a primary data digger and documentation as a secondary data digger. The collected data is processed and analyzed. Data analysis using univariate and bivariate analysis. Univariate analysis is to describe teacher commitment and work behavior. While this bivariate analysis was used to analyze the relationship between commitment and work behavior of teachers in SDN 3B Kemuning Banjarbaru. The results of the study show that (1). A small number of SDN 3 Kemuning Banjarbaru teachers have high commitment, quite a large number of teachers have commitments in the medium category, and the smallest part is still teachers who have low commitment. (2). A large number of teacher teachers at SDN Kemuning 3 Banjarbaru have had good and quite large behaviors and teachers have good behavior and no teacher has bad behavior. (3). There is a significant relationship between commitment and work behavior of teachers in SDN 3 Kemuning Banjarbaru. Based on the findings above, it is suggested: (1). The Principal can improve teacher work effectiveness by first increasing the ability of teachers through seminars, workshops, workshops and so on so that teachers can increase their knowledge and skills (2) School Supervisors can provide guidance to teachers and Principals continuously in order to improve their effectiveness.